2019
DOI: 10.3390/jcm8060784
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Long-Term Effects of Transgender Hormone Therapy on Bone Markers and Bone Mineral Density and Their Potential Effects in Implant Therapy

Abstract: This study seeks to evaluate the long-term effects of pharmacologic therapy on the bone markers and bone mineral density of transgender patients and to provide a basis for understanding its potential implications on therapies involving implant procedures. Following the referred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and well-defined PICOT (Problem/Patient/Population, Intervention, Comparison, Outcome, Time) questionnaires, a literature search was completed for articles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 72 publications
0
14
0
1
Order By: Relevance
“…Today, three-dimensional porous scaffolds can be produced that possess shape memory effects for bone tissue engineering. Both in vitro and in vivo studies revealed a significant influence of scaffold order and symmetry onto cell differentiation and proliferation [223][224][225][226][227]. Although, the systemic effect of the immune system can reject the biomaterial and that could lead to failure in vivo, this effect is not further considered and discussed.…”
Section: Scaffolds Used In Osteoporosis Treatmentmentioning
confidence: 99%
“…Today, three-dimensional porous scaffolds can be produced that possess shape memory effects for bone tissue engineering. Both in vitro and in vivo studies revealed a significant influence of scaffold order and symmetry onto cell differentiation and proliferation [223][224][225][226][227]. Although, the systemic effect of the immune system can reject the biomaterial and that could lead to failure in vivo, this effect is not further considered and discussed.…”
Section: Scaffolds Used In Osteoporosis Treatmentmentioning
confidence: 99%
“…Questions related to bone health are also discussed, as in the study by Delgado-Ruiz et al (2019). They analyzed the long-term effects of drug therapy on bone health parameters and bone mineral density in transgender patients.…”
Section: Scientific Evidence Involving Health and Gender Identitymentioning
confidence: 99%
“…Esta população tende a ter alterações bucais, de etiologia multifatorial podendo se derivar desde o uso terapia hormonal utilizada por pacientes com disforia de gênero 12 , até o abuso de substâncias, transtornos alimentares, transtornos depressivos e/ou ansiosos e infecções sexualmente transmissíveis. O cirurgião-dentista deve estar apto a diagnosticar e tratar tais patologias, a fim de promover a cura de seus pacientes e orientá-los quanto aos fatores de risco para prevenir recidivas das lesões orais 13 .…”
Section: Introductionunclassified